2010
DOI: 10.1128/jvi.01211-10
|View full text |Cite
|
Sign up to set email alerts
|

Swine Influenza H1N1 Virus Induces Acute Inflammatory Immune Responses in Pig Lungs: a Potential Animal Model for Human H1N1 Influenza Virus

Abstract: Pigs are capable of generating reassortant influenza viruses of pandemic potential, as both the avian and mammalian influenza viruses can infect pig epithelial cells in the respiratory tract. The source of the current influenza pandemic is H1N1 influenza A virus, possibly of swine origin. This study was conducted to understand better the pathogenesis of H1N1 influenza virus and associated host mucosal immune responses during acute infection in humans. Therefore, we chose a H1N1 swine influenza virus, Sw/OH/243… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
146
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(154 citation statements)
references
References 56 publications
5
146
3
Order By: Relevance
“…Similar to these observations, we previously isolated progenitor epithelial cells from the lungs of pigs that were also surrounded by mesenchymal cells. 27 Not much is known about the exact relationship between co-existing epithelial and mesenchymal cells in this culture system. Recent publications demonstrated that MSCs can differentiate into epithelial cell phenotypes in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to these observations, we previously isolated progenitor epithelial cells from the lungs of pigs that were also surrounded by mesenchymal cells. 27 Not much is known about the exact relationship between co-existing epithelial and mesenchymal cells in this culture system. Recent publications demonstrated that MSCs can differentiate into epithelial cell phenotypes in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Stained cells were acquired by C6 flow cytometer (BD Accuri Cytometers) and analyzed using CFlow Ò plus Software (Accuri). 27 Preparation of lung MSC-CM We collected CM from porcine lung MSCs cultures as described previously. 54 Briefly, porcine lung-MSCs were grown and expanded in DMEM containing 10% FBS.…”
Section: Phenotyping Of Cells By Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Viral mutation rates in swine have been used to inform predictive models of viral behavior affecting humans (Chang et al 2002). Swine manifest similar influenza pathogenesis as observed in humans (Khatri et al 2010) and can serve as models of immunization to aide in the understanding of individual and population (herd) immunity (Masic et al 2010;Hyland et al 2004).…”
Section: Immune Systemmentioning
confidence: 99%
“…Swine flu is the name for the respiratory infection caused by influenza A virus subtype H1N1. This subtype represents the genetic combination of avian, human and swine flu (3). In contrast to the typical swine flu, this form of the virus is transmitted from human to human.…”
Section: Introductionmentioning
confidence: 99%